Beyond the Language Classroom: Researching MOOCs and Other Innovations 2017
DOI: 10.14705/rpnet.2017.mooc2016.672
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a MOOC into the postgraduate ELT curriculum: reflecting on students’ beliefs with a MOOC blend

Abstract: T his chapter builds on the outcomes of a blended learning action-research project in its third iteration (academic year 2015-16). The FutureLearn Massive Open Online Course (MOOC) Understanding Language: Learning and Teaching was integrated into the curriculum of the Master of Arts (MA) in English Language Teaching (ELT) at Coventry University (UK). The MOOC was designed by the University of Southampton in collaboration with the British Council and many of its topics appeared to coincide with those on the MA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 9 publications
(6 reference statements)
3
5
0
Order By: Relevance
“…Based on the qualitative findings, most of the participants said that this could be a good idea, stating that they would like the MOOC-based FC model to be integrated into their ELT program. In accordance with the present results, previous studies have also indicated that participants hold positive views about integrating a MOOC into their traditional classroom lectures (Bruff et al, 2013;Ghadiri et al, 2013;Orsini-Jones, Conde Gafaro, & Altamimi, 2017;Xinying, 2017;Yousef et al, 2015).…”
Section: Discussion Of Findings For the 2 Nd Research Questionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on the qualitative findings, most of the participants said that this could be a good idea, stating that they would like the MOOC-based FC model to be integrated into their ELT program. In accordance with the present results, previous studies have also indicated that participants hold positive views about integrating a MOOC into their traditional classroom lectures (Bruff et al, 2013;Ghadiri et al, 2013;Orsini-Jones, Conde Gafaro, & Altamimi, 2017;Xinying, 2017;Yousef et al, 2015).…”
Section: Discussion Of Findings For the 2 Nd Research Questionsupporting
confidence: 92%
“…The results are in line with that of Orsini-Jones, Conde Gafaro, and Altamimi (2017) who found in their study that students perceived the MOOC blend as a positive addition to their existing face-to-face courses as they enjoyed the flexibility in the MOOCs that keep additional learning materials within easy reach and provide them with a comprehensive e-learning platform. A possible explanation for these results might be that the participants attached significance to communicative aspects of learning across national and cultural borders, which is promoted by MOOCs.…”
Section: Discussion Of Findings For the 2 Nd Research Questionsupporting
confidence: 89%
See 1 more Smart Citation
“…The South-North dialogue between British and international students based in the UK and studying on an MA in English Language Teaching and Applied Linguistics and their counterparts based in other countries overseas (China and Spain in academic year 2020–2021 for example), highlighted interesting intercultural ELT aspects and fostered a discussion regarding what ELT curriculum should include and stress. The critique of the current content of traditional ELT curricula, was underpinned by the shared use of an existing FutureLearn MOOC (Massive Open Online Course): Understanding Language: Learning and Teaching (by the University of Southampton and the British Council), in a unique COIL-MOOC blend—BMELTET- pioneered at Coventry University (Orsini-Jones et al, 2017; Orsini-Jones & Cerveró Carrascisa, 2019). The aim of BMELTET has been to research how a holistic approach to the integration of technology into ELT education can impact on students’ ways of thinking and relating by providing them with the opportunity to engage with a global ELT community of practice both via COIL and linked to a MOOC that has over 200,000 participants from all over the world, and, in so doing, rethink ELT in an autonomous way to find ways in which English can be best taught in their respective contexts.…”
Section: Illustrative Perspectivesmentioning
confidence: 99%
“…the bestselling Richards & Rodgers, 2014) do not appear to address the online dimension, its affordances and how transformative effective engagement with technology can prove to be for teachers' agency. BMELTET aims to illustrate that teachers' cognition, triggered by active learning with a MOOC/COIL blend, can be empowering for ELT practitioners, can help them develop critical digital literacy and thus support them in the troublesome journey across the uncertain terrain of autonomy in language learning and teaching, as autonomy had previously been identified as a threshold concept for them by 'expert students' (Orsini- Jones et al, 2017a;2017b and2017c). Jiao, for example, (2018) argues that autonomy is particularly challenging as a concept for students who, like himself, come from a teacher-centred Confucian learning tradition.…”
Section: The Role-reversal Coil Threshold Concepts and Action-researc...mentioning
confidence: 99%